2023
DOI: 10.1371/journal.pone.0282847
|View full text |Cite
|
Sign up to set email alerts
|

Water level prediction using soft computing techniques: A case study in the Malwathu Oya, Sri Lanka

Abstract: Hydrologic models to simulate river flows are computationally costly. In addition to the precipitation and other meteorological time series, catchment characteristics, including soil data, land use, land cover, and roughness, are essential in most hydrologic models. The unavailability of these data series challenged the accuracy of simulations. However, recent advances in soft computing techniques offer better approaches and solutions at less computational complexity. These require a minimum amount of data, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…These studies have shown that fuzzy logic can capture the non-linear and uncertain nature of financial markets, leading to more accurate predictions compared to traditional statistical methods. In the context of rice production in Sri Lanka, fuzzy logic could offer a valuable tool for modeling the complex interactions between economic factors and agricultural outcomes, providing insights that can enhance the resilience and sustainability of rice cultivation in the face of economic uncertainties [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that fuzzy logic can capture the non-linear and uncertain nature of financial markets, leading to more accurate predictions compared to traditional statistical methods. In the context of rice production in Sri Lanka, fuzzy logic could offer a valuable tool for modeling the complex interactions between economic factors and agricultural outcomes, providing insights that can enhance the resilience and sustainability of rice cultivation in the face of economic uncertainties [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that fuzzy logic can capture the non-linear and uncertain nature of financial markets, leading to more accurate predictions compared to traditional statistical methods. In the context of rice production in Sri Lanka, fuzzy logic could offer a valuable tool for modeling the complex interactions between economic factors and agricultural outcomes, providing insights that can enhance the resilience and sustainability of rice cultivation in the face of economic uncertainties [32,33].…”
Section: Introductionmentioning
confidence: 99%